Anti-fatigue-fracture hydrogels - Lin, Shaoting (Sci Adv, 2019)
The emerging applications of hydrogels in devices and machines require hydrogels to maintain robustness under cyclic mechanical loads. Whereas hydrogels have been made tough to resist fracture under a single cycle of mechanical load, these toughened gels still suffer from fatigue fracture under multiple cycles of loads. The reported fatigue threshold for synthetic hydrogels is on the order of 1 to 100 J/m(2). We propose that designing anti-fatigue-fracture hydrogels requires making the fatigue crack encounter and fracture objects with energies per unit area much higher than that for fracturing a single layer of polymer chains. We demonstrate that the controlled introduction of crystallinity in hydrogels can substantially enhance their anti-fatigue-fracture properties. The fatigue threshold of polyvinyl alcohol (PVA) with a crystallinity of 18.9 weight % in the swollen state can exceed 1000 J/m(2).